2022
DOI: 10.3390/nu14235171
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mTOR Signaling by Dietary Polyphenols in Obesity Prevention

Abstract: Dietary polyphenols can be utilized to treat obesity and chronic disorders linked to it. Dietary polyphenols can inhibit pre-adipocyte proliferation, adipocyte differentiation, and triglyceride accumulation; meanwhile, polyphenols can also stimulate lipolysis and fatty acid β-oxidation, but the molecular mechanisms of anti-obesity are still unclear. The mechanistic target of rapamycin (mTOR) is a protein kinase that regulates cell growth, survival, metabolism, and immunity. mTOR signaling is also thought to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…Different polyphenols have different sugar units and acylated sugars at different positions on their main chains. At present, polyphenols are widely used in health food and medicine because of their beneficial impact on various biological functions and their lack of side effects on human body [12,13]. In recent years, with the study and utilization of the active substances of Allium plants, it has been found that most of them have antioxidant, anti-tumor, antibacterial and lipid-lowering effects, as well as contributing to cardiovascular disease prevention and other biological functions [2,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Different polyphenols have different sugar units and acylated sugars at different positions on their main chains. At present, polyphenols are widely used in health food and medicine because of their beneficial impact on various biological functions and their lack of side effects on human body [12,13]. In recent years, with the study and utilization of the active substances of Allium plants, it has been found that most of them have antioxidant, anti-tumor, antibacterial and lipid-lowering effects, as well as contributing to cardiovascular disease prevention and other biological functions [2,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the collected data focused on the molecular mechanisms by which dietary polyphenols target the mTOR signaling pathway. mTOR, a protein kinase that regulates cell growth, survival, metabolism, and immunity, seems to mediate the polyphenol’s anti-obesity effect by modulating lipid metabolism, adipogenesis, and inflammation [ 10 ].…”
mentioning
confidence: 99%